Experienced and Anticipated Discrimination and Social Functioning in Persons With Mental Disabilities in Kenya: Implications for Employment - Ebuenyi, Ikenna D.; Regeer, Barbara J.; Ndetei, David M.; Bunders-Aelen, Joske F. G.; Guxens, Mònica (Frontiers in Psychiatry, 2019)
Introduction: Persons with mental illness experience social life restriction and stigma that may have implications for their work ability. The aims of this study are i) to report experienced and anticipated discrimination and social functioning in persons with mental disabilities in Kenya and ii) to investigate the association between experienced and anticipated discrimination, social functioning, and employment in this population. Materials and Methods: Cross-sectional study design where we randomly recruited 72 persons with mental illness through two networks of persons with psychosocial disabilities in Kenya. Experienced and anticipated discrimination were measured using the Discrimination and Stigma Scale version 12 (DISC 12) while social functioning was measured using the Social Functioning questionnaire (SFQ). Results: Experienced discrimination was reported by 81.9% in making or keeping friends, 69.7% and 56.3% in finding or keeping job respectively, and 63.3% in dating or having an intimate relationship. Anticipated discrimination stopped 59.2% from applying for work, 40.8% from applying for education or training courses, and 63.4% from having a close personal relationship. Females reported an overall higher experienced discrimination than males. Unemployed participants had slightly increased rates of experienced and anticipated discrimination (9.5 vs. 9.1 and 2.5 vs. 2.3, respectively) (p>0.05), while there was a significant association between impaired social functioning and unemployment (14.0 vs. 11.2 (p=0.037)). Conclusion: The rates of experienced and anticipated discrimination faced by persons with mental disabilities in Kenya is high and with significant gender disparity. Although no strong associations were observed between experienced and anticipated discrimination and employment, impaired social functioning of persons with mental disabilities seems to have implications for employment. Further research is essential to understand the predictors of the discrimination and measures to reduce them in person with psychosocial disabilities.